2022
DOI: 10.1186/s12872-022-02814-3
|View full text |Cite
|
Sign up to set email alerts
|

EGR2 is a hub-gene in myocardial infarction and aggravates inflammation and apoptosis in hypoxia-induced cardiomyocytes

Abstract: Background Myocardial infarction (MI) is characterized by coronary artery occlusion, ischemia and hypoxia of myocardial cells, leading to irreversible myocardial damage. Therefore, it is urgent to explore the potential mechanism of myocardial injury during the MI process to develop effective therapies for myocardial cell rescue. Methods We downloaded the GSE71906 dataset from GEO DataSets, and the R software was used to identify the differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…EGR2, which belongs to the EGR family, has pro-inflammatory and pro-apoptotic effects. EGR2 can directly activate the expression of pro-apoptotic proteins such as BCL2 family and BINP3L, and can also upregulate inflammatory proteins such as IFNG and IL6 50 . Studies have shown that inhibition of EGR2 expression via lncRNA and miRNA can alleviate cardiac apoptosis and protect the heart from ischemic injury 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…EGR2, which belongs to the EGR family, has pro-inflammatory and pro-apoptotic effects. EGR2 can directly activate the expression of pro-apoptotic proteins such as BCL2 family and BINP3L, and can also upregulate inflammatory proteins such as IFNG and IL6 50 . Studies have shown that inhibition of EGR2 expression via lncRNA and miRNA can alleviate cardiac apoptosis and protect the heart from ischemic injury 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…17 EGR2 is identified to aggravate hypoxia-induced cardiomyocyte inflammation and apoptosis, which is a hub gene in myocardial infarction. 18 In addition, this method has also been implemented in cervical cancer and breast cancer. 19,20 In this study, using bioinformatic analysis, we selected the key gene GNL3L, which may be of vital importance in the progression of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial stroke results in cardiomyocyte cell death due to hypoxia or ischemia caused by an unbalance between the oxygen deposition and requirement in the heart. This ischemia may be caused by an occlusion of the coronary artery with consequent cell death and inflammation [ 94 , 95 , 96 ].…”
Section: Impact Of Lncrnas and Circrnas In Ers And Upr Response On Ca...mentioning
confidence: 99%